2018
DOI: 10.1136/annrheumdis-2018-213418
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells in early rheumatoid arthritis associate with disease severity and support B cell autoantibody production

Abstract: Synovial MCs identify early RA patients with a severe clinical form of synovitis characterised by the presence of ELS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
42
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 56 publications
9
42
0
Order By: Relevance
“…Mast cells have so far not been a major focus of RA research; results from in vitro cellular experiments and in vivo animal studies have been inconsistent. Synovial mast cells have been shown to be associated with inflammation, autoantibody production, and high disease activity in early RA [25]. In this study, we investigated the role of mast cells in bone destruction during RA.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells have so far not been a major focus of RA research; results from in vitro cellular experiments and in vivo animal studies have been inconsistent. Synovial mast cells have been shown to be associated with inflammation, autoantibody production, and high disease activity in early RA [25]. In this study, we investigated the role of mast cells in bone destruction during RA.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells, strategically located in different sections of the human heart [51,52] and atherosclerotic plaque [32,33], are involved in different phases of atherosclerosis and myocardial infarction. These cells can be involved in several autoimmune disorders, such as rheumatoid arthritis [37], coeliac disease [94], multiple sclerosis [124], and bullous dermatoses [125]. Mast cell-nerve communications are involved in stress, pain, pruritus [126,127], and in inflammatory bowel diseases [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these cells can be activated by different viral [25,26] and bacterial proteins [27,28] and thereby represent a potentially important cell during microbial infections. Therefore, the spectrum of diseases in which mast cells and their mediators have been implicated has extended to include bacterial, fungal, viral, and helminth infections [26,[29][30][31]; several diseases of the cardiovascular [14,32,33] and gastrointestinal systems [34][35][36]; and the joints [37,38]. Figure 1 schematically summarizes the wide spectrum of pathophysiological conditions in which mast cells and their mediators have been implicated during the last decades.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to other immune cell populations, MCs have been suggested to play a crucial role, because MCs are abundant in inflamed synovial joints of RA patients, especially around blood vessels in the synovial sub-lining, at the cartilage-pannus junction at sites of cartilage erosions, and in joint fluid (Figure 1C) [comprehensively reviewed by Rivellese et al (162)]. Importantly, some of the clinical studies observed a correlation of MC numbers with joint inflammation and disease activity (163)(164)(165)(166)(167). In addition, the levels of MC mediators, including histamine and tryptase, were significantly increased in the synovial tissue of RA patients ( Figure 1C) (8,168,169).…”
Section: Rheumatoid Arthritismentioning
confidence: 99%